2008
DOI: 10.1016/j.jcmg.2008.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Limb Stress-Rest Perfusion Imaging With Contrast Ultrasound for the Assessment of Peripheral Arterial Disease Severity

Abstract: Perfusion imaging of limb skeletal during exercise and measurement of absolute flow reserve can provide valuable information on the severity PAD. This strategy may be useful for evaluating the total impact of disease in patients with complex disease or those with coexisting functional abnormalities of flow regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
102
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 28 publications
8
102
1
Order By: Relevance
“…We hypothesize that the changes in capillary structure (BM thickening, collapsed lumen, swollen EC) contribute to impaired microvascular muscle perfusion in PAD (33). This is likely to impede the diffusion of oxygen and nutrients into skeletal muscle fibers of the IC patients, thereby compromising their energy supply and contractile capacity.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that the changes in capillary structure (BM thickening, collapsed lumen, swollen EC) contribute to impaired microvascular muscle perfusion in PAD (33). This is likely to impede the diffusion of oxygen and nutrients into skeletal muscle fibers of the IC patients, thereby compromising their energy supply and contractile capacity.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, laser Doppler flowmetry can be used to assess the local microcirculation, 8 and contrast-enhanced ultrasound has been introduced recently for the determination of tissue perfusion in patients with PAD. 23,24 Moreover, functional assessment with magnetic resonance imaging has been described in single individuals but not yet evaluated in a clinical trial. 8,25 Apart from the invasive measurement of antegrade flow velocity in a single patient in the early days of angiogenesis research (certainly without balloon occlusion), 26 no attempts have been made to directly quantify the collateral circulation of the lower limb.…”
Section: Discussionmentioning
confidence: 99%
“…72 Similarly, imaging studies using MRI or contrast-enhanced ultrasound have demonstrated lower microvascular flow in the calf musculature in PAD patients. 73, 74 Exercise blood flow measured by contrast ultrasound was related to claudication time in a treadmill test. 74 Also, reduced skeletal muscle blood flow as measured by MR during exercise was associated with impaired 6-minute walking time.…”
Section: Systemic and Local Inflammationmentioning
confidence: 99%
“…73, 74 Exercise blood flow measured by contrast ultrasound was related to claudication time in a treadmill test. 74 Also, reduced skeletal muscle blood flow as measured by MR during exercise was associated with impaired 6-minute walking time. 43 Taken together, evidence from clinical investigations supports the concept that microcirculatory dysfunction affects limb function in patients with PAD, and that enhanced calf blood flow may be a therapeutic avenue.…”
Section: Systemic and Local Inflammationmentioning
confidence: 99%